2010
DOI: 10.1007/s10725-010-9497-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of nuclear proteins during dehydration of the resurrection plant Xerophyta viscosa

Abstract: Xerophyta viscosa (family Velloziaceae) is a monocotyledonous poikilochlorophyllous desiccation tolerant plant capable of surviving drying its leaf tissue to 5% relative water content (RWC) for prolonged periods and resuming full physiological activity upon rehydration. X. viscosa and other resurrection plants are excellent model systems for the study of desiccation tolerance mechanisms. In this work, the X. viscosa nuclear protein profile was investigated in response to dehydration stress using 2D gel electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 106 publications
1
28
0
Order By: Relevance
“…However, continuing technical improvements have largely overcome these difficulties in various explants, including the embryo [Masuda et al, 1991;Yamaguchi et al, 1992;Busk and Pages, 1997], endosperm [Ferreira et al, 2006;Li et al, 2008], seed [Riggs et al, 1989], seed coat [Renouard et al, 2012], leaf [e.g. Cushman, 1995;Zhang et al, 1995;Abdalla et al, 2009Abdalla et al, , 2010Sikorskaite et al, 2013], and root meristem [Silva et al, 2010], and in in vitro cultured cells [Willmitzer and Wagner, 1981]. Currently used extraction protocols directed at nuclear proteins use mechanical homogenization, filtration to remove large detritus, pelleting, suspension in a non-ionic detergent, and finally separation by density gradient centrifugation [for review see Narula et al, 2013].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, continuing technical improvements have largely overcome these difficulties in various explants, including the embryo [Masuda et al, 1991;Yamaguchi et al, 1992;Busk and Pages, 1997], endosperm [Ferreira et al, 2006;Li et al, 2008], seed [Riggs et al, 1989], seed coat [Renouard et al, 2012], leaf [e.g. Cushman, 1995;Zhang et al, 1995;Abdalla et al, 2009Abdalla et al, , 2010Sikorskaite et al, 2013], and root meristem [Silva et al, 2010], and in in vitro cultured cells [Willmitzer and Wagner, 1981]. Currently used extraction protocols directed at nuclear proteins use mechanical homogenization, filtration to remove large detritus, pelleting, suspension in a non-ionic detergent, and finally separation by density gradient centrifugation [for review see Narula et al, 2013].…”
mentioning
confidence: 99%
“…Currently used extraction protocols directed at nuclear proteins use mechanical homogenization, filtration to remove large detritus, pelleting, suspension in a non-ionic detergent, and finally separation by density gradient centrifugation [for review see Narula et al, 2013]. This sort of scheme has provided descriptions of the Arabidopsis thaliana [Bae et al, 2003;Jones et al, 2009], hot pepper [Lee et al, 2006], rice [Tan et al, 2007;Li et al, 2008;Aki and Yanagisawa, 2009;Choudhary et al, 2009], barrel clover [Repetto et al, 2008], maize [Casati et al, 2008], black-stick lily [Abdalla et al, 2010;Abdalla and Rafudeen, 2012], soybean [Cooper et al, 2011], flax [Renouard et al, 2012], and chickpea [Pandey et al, 2006;Varshney et al, 2013] nuclear proteomes. Typically, however, the number of proteins identified has been rather low, ranging from 56 (hot pepper) to 657 (rice) [Lee et al, 2006;Aki and Yanagisawa, 2009].…”
mentioning
confidence: 99%
“…Colville and Kranner (2010) provide an excellent review of responses of desiccation tolerant plants and seeds to oxidative stress, showing that such organisms are robust models for the study of protein redox regulation. Abdalla et al (2010) have identified nuclear proteins significantly up-regulated during drying of the resurrection plant Xerophyta viscosa, these data confirming that DT is indeed characterised and controlled by a multiple gene response. A comprehensive review of research conducted over the past 17 odd years on the resurrection grass Sporobolus stapfianus, put into context of how this information can be utilized for devising strategies for improved tolerance of water deficit as well as enhancing growth rates and biomass production in future applied studies is provided in the paper of Blomstedt et al (2010).…”
mentioning
confidence: 61%
“…Typically such studies pose specific research questions and are conducted using discipline specific approaches on a single species, but often reflect some common questions and strategies associated with research into desiccation tolerance. Papers within this issue report on stresses associated with water deficit, such as the mechanical stress of plasmolysis (Koster et al 2010), oxidative stresses, including those associated with light (Aidar et al 2010;Proctor 2010;Kamies et al 2010;Colville and Kranner 2010) and the protective responses generated in response to those stresses, or take a more global approach of searching for genes and gene products up regulated in response to stress (Abdalla et al 2010). In addition to furthering our understanding of stresses and associated protection these works add important information to the field.…”
mentioning
confidence: 99%
See 1 more Smart Citation